EKSPLORASI ETNOMATEMATIKA PADA BUDAYA ARAK JODHANG NYADRAN MAKAM SEWU KABUPATEN BANTUL - Faizah, Hilmy; Suparni, Suparni (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
Ethnomatematics is an approach in learning that links mathematics with a culture. Applying ethnomathematics in class is very important, because it can make it easier for students to understand mathematical material by linking it to real world problems. The Arak Jodhang culture is one of the cultures in the form of activities of troop convoys wearing soldier's clothing carrying jodhang. In this culture, various mathematical concepts are found. The researcher is interested in conducting this research with the aim of exploring the mathematical concepts found in the Arak Jodhang Nyadran Makam Sewu, Bantul Regency. The method used in this study is explorative with an ethnographic approach. Data collection was carried out by means of observation, documentation, interviews, and literature study. The results of this study indicate that there are various mathematical concepts in the Arak Jodhang Nyadran Makam Sewu culture and can be used in teaching mathematics in class. The concepts found include: the concept of circles, triangles, quadrilaterals, geometric shapes, straight lines, and geometric transformations.